2006
DOI: 10.2975/30.2006.15.22
|View full text |Cite
|
Sign up to set email alerts
|

An Ethnographic Study of Job Seeking Among People with Severe Mental Illness.

Abstract: An ethnographic study employing intensive participant observation methods identified critical differences in styles of searching for competitive employment among people with severe mental illness and explored the social/cultural correlates of these job-seeking styles. Propensity for active job seeking was strongly associated with younger age, with participants' involvement in interdependent kin networks or households, with ethno-racial minority background, and with capacity for coherent discourse. Active job s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 19 publications
0
62
0
1
Order By: Relevance
“…Their families may in turn try to minimize conflict by withdrawing or choosing to tolerate or ignore substance abuse (Copello, 2003). Under any of these conditions, co-morbid individuals have an increased risk of relapse (Mueser et al, 1992;Alverson et al, 2000). In fact, interpersonal conflict and social pressure are generally identified as two of the biggest antecedents of substance abuse relapse (Copello, 2003).…”
Section: How Social Network and Social Support Systems Mattermentioning
confidence: 99%
“…Their families may in turn try to minimize conflict by withdrawing or choosing to tolerate or ignore substance abuse (Copello, 2003). Under any of these conditions, co-morbid individuals have an increased risk of relapse (Mueser et al, 1992;Alverson et al, 2000). In fact, interpersonal conflict and social pressure are generally identified as two of the biggest antecedents of substance abuse relapse (Copello, 2003).…”
Section: How Social Network and Social Support Systems Mattermentioning
confidence: 99%
“…An ethnographic study of job-seeking among people with severe mental health problems (Alverson et al, 2006) revealed that, irrespective of the vocational rehabilitation intervention they were receiving, individuals fell into two categories: active job-seekers and passive job-seekers -active job-seekers did well vocationally whereas passive job-seekers made little or no progress. There is some initial evidence showing that it is possible to increase the motivation and/or self-efficacy in job-seeking behaviours of people with severe mental health problems through the use of cognitive-behavioural therapy (Gould et al, 2001;Lysaker et al, 2005;Lysaker et al, 2006), cognitive training (McGurk et al, 2005) and motivational interviewing (Debring et al, 2006;Larson et al, 2006).…”
Section: Client Factors: Diagnosis Is Not Importantmentioning
confidence: 99%
“…They may be unaware of job restrictions and employment saturation [6][7]19] and spend time focused on lowprobability options. They may have expectations for employment that are unrealistic for entry-level positions [17] or may take a passive approach in searching for employment [22]. Additionally, they may lack the confidence to actively job search, assuming the effort is not worth the rejection [20][21]23].…”
Section: Introductionmentioning
confidence: 99%